High incidence of hepatocellular carcinoma and postoperative complications in patients with nonalcoholic steatohepatitis as a primary indication for deceased liver transplantation. Issue 2 (February 2019) - Kern, Barbara; Feurstein, Benedikt; Fritz, Josef; Fabritius, Cornelia; Sucher, Robert; Graziadei, Ivo; Bale, Reto; Tilg, Herbert; Zoller, Heinz; Newsome, Philip; Eschertzhuber, Stephan; Margreiter, Raimund; et al.
Abstract : Background and aims: Nonalcoholic steatohepatitis (NASH) is an increasingly prevalent indication for liver transplantation (LT) across the world. The relative outcomes following transplantation are poorly described in this cohort. We aimed to analyze the incidence and outcome of LT for NASH as compared with other indications. Patients and methods: This is a retrospective analysis of 513 patients who underwent deceased-donor, adult LT between 2002 and 2012 as recorded at the Medical University of Innsbruck, Austria. Results: The prevalence of NASH cirrhosis as indication for liver transplantation was 12.7% (65/513). Patient survival in patients with NASH was comparable to other indications, including alcohol-induced liver steatosis (ALD) and hepatitis C virus (HCV) ( P =0.208). Patients with NASH were older, had a higher model of end-stage liver disease score and a higher BMI, but patient survival and graft survival were equivalent to other indications. Patients with hepatocellular carcinoma (HCC) as primary indication for liver transplantation showed significantly inferior overall survival as compared with the other indications ( P =0.003). Patients with NASH had coexisting HCC in 53.7% of cases, whereas HCC in ALD, HCV and other indications was prevalent in 31.2, 47.7, and 34.5%, respectively ( P <0.0001). Patients with NASH had a higher incidence of advanced HCCs (outside the Milan criteria) than patients with ALD, HCV, and other indications ( P =0.034). P ostoperative complications were significantly higher in the NASH cohort ( P =0.048). Conclusion: In this single-center LT database analysis, patients with NASH have a higher incidence and a more rapid progression of HCC as well as an increased incidence of postoperative complications. Our findings warrant confirmation by others.